2019
DOI: 10.25077/adj.v7i1.129
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Berkumur Dengan Larutan Teh Hijau dan Teh Hitam Terhadap pH Saliva

Abstract: The prevalence of caries in Indonesia has increased by 53.53% from 2013 to 2018. Low salivary pH (potential of Hydrogen) is one of the main causes of dental caries. Acid as metabolic product of oral microorganism can decrease the salivary pH. The purpose of this paper is to determine the effect of gargling with green and black tea solutions on salivary pH. The increasing of salivary pH linear to salivary secretion. Gargling with green tea or black tea is one of the ways that can increase salivary secretion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Catechins can inhibit the growth of Streptococcus mutans bacteria by binding to components of the bacterial cell wall and damaging the lipid bilayer thereby increasing salivary pH due to a reduced number of bacteria that can produce acid in the oral cavity. 17 The results of statistical tests in this study showed a significant difference in effectiveness between pomegranate peel extract and green tea on salivary pH. If pomegranate peel extract is able to increase the pH of saliva, it can minimize the occurrence of an acidic circumstances in the oral cavity so as to prevent dental caries and can be used as an alternative mouthwash with herbal ingredients that are safe for long-term use and minimize various side effects that can be caused.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Catechins can inhibit the growth of Streptococcus mutans bacteria by binding to components of the bacterial cell wall and damaging the lipid bilayer thereby increasing salivary pH due to a reduced number of bacteria that can produce acid in the oral cavity. 17 The results of statistical tests in this study showed a significant difference in effectiveness between pomegranate peel extract and green tea on salivary pH. If pomegranate peel extract is able to increase the pH of saliva, it can minimize the occurrence of an acidic circumstances in the oral cavity so as to prevent dental caries and can be used as an alternative mouthwash with herbal ingredients that are safe for long-term use and minimize various side effects that can be caused.…”
Section: Discussionmentioning
confidence: 66%
“…14 This is not much different from the benefits of green tea in Putri's research in 2019 which has the potential as an anticariogenic so that it can increase the pH of saliva due to its catechin content. 17 The first study using pomegranate peel extract showed an increase in salivary pH (mean salivary pH became 6.89 from the initial pH of 6.8). The results of this study are in line with the research of Umar et al in 2016 and Kadam et al 2019 which stated that rinsing pomegranate peel extract was able to increase the pH of saliva.…”
Section: Discussionmentioning
confidence: 99%
“…You can do various ways to rinse your mouth, generally using plain water or mouthwash, or using other ingredients. One of them is tea Gargling with tea has great benefits in preventing dental and oral diseases (8) .…”
Section: Introductionmentioning
confidence: 99%
“…After mineral water, tea is the second drink most consumed by humans (8) . One type of tea that is often consumed so far is green tea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation